重構公共與私人界限：公共健康作為人口層面視角的形而上學框架——對麥凱“公共健康倫理學：ー種藝術的現狀”ー文的評論: Redefining Public and Private Boundaries: Public Health as a Metaphysical Framework of Population-level Perspective: A Commentary on MacKay’s “Public Health Ethics: The State of the Art” - WANG, Shuai (International Journal of Chinese & Comparative Philosophy of Medicine, 2024)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. This commentary explores Kathryn MacKay’s concept of public health as a metaphysical framework that shifts private issues, such as smoking and domestic violence, into the area of public health. Using a third-person, population-level perspective, this paper examines the ethical basis for reframing such behaviours as public health issues, advocating for stricter regulation of smoking and systemic responses to domestic violence. MacKay’s framework offers valuable support for advancing comprehensive public health policies, which is particularly relevant in China.